Consequences of COVID‐19 pandemic on solid waste management: Scenarios pertaining to developing countries. Issue 4 (12th July 2021) - Almulhim, Abdulaziz I.; Ahmad, Imran; Sarkar, Silpi; Chavali, Murthy
Abstract: Undoubtedly the most searched and spoken word of last year is coronavirus disease 2019 (COVID‐19), which initially originated in Wuhan, China near the end of 2019. COVID‐19 is a disease caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). Albeit almost all countries shut down their borders to prevent rapid spread of the virus. However, the number of cases continues to increase in developing countries at a faster rate due to community and cluster transmission. The severity of this epidemic made it a pandemic as it progressed to over 200 countries. The World Health Organization (WHO), governments, and national disease control and prevention units worked together to break the chain and are working to contain the catastrophic impact of COVID‐19. They formulated and recommended various guidelines like social distancing, frequent hand washing, and social distancing to inhibit the spread of the virus. WHO also advised that the general population and medical personnel wear face masks, face shields, gloves, and aprons. As a result, this waste category has substantially increased and, if not disposed of properly, may cause the infection or help to catalyze COVID‐19. In developing countries, poor solid waste management may aggravate chances of spreading COVID‐19. Sustainable solid waste management is a critical parameter for the health, wellbeing, and development of society. The measures adopted to contain and restrict the spread of the COVID‐19 pandemic and minimize the degrees of freedom in commercial events affected solid waste management considerably. During this crucial time, the services provided by waste management agencies and personnel are invaluable and these services help to prevent the improper disposal of waste, which may lead to health risks due to the spread of COVID. COVID‐19 is a new and novel virus and experts are learning more about it overtime and with evolving science. This review paper provides insight into different types of solid wastes generated during the pandemic, their consequences, and the implication of various policies.